Climate change conditions the selection of rust-resistant candidate wild lentil populations for in situ conservation - Civantos-Gómez, Iciar; Rubio Teso, María Luisa; Galeano, Javier; Rubiales, Diego; Iriondo, José María; García-Algarra, Javier (Frontiers in Plant Science, 2022)
Crop Wild Relatives (CWR) are a valuable source of genetic diversity that can be transferred to commercial crops, so their conservation will become a priority in the face of climate change. Bizarrely, in situ conserved CWR populations and the traits one might wish to preserve in them are themselves vulnerable to climate change. In this study, we used a quantitative predictive characterization approach, based on machine learning, to project the rust resistance of CWR populations of lentils in the Mediterranean basin. Rust-resistant candidate populations were subsequently explored to assess their future vulnerability to changes in environmental conditions that might result in the loss of this trait. For this purpose, the same models were applied under future climate conditions predicted by IPCC (Intergovernmental Panel on Climate Change). Rust-resistant candidate populations under current conditions that also kept optimal environmental conditions for the future preservation of the target trait were selected as best candidates for further evaluation and in situ conservation. Patterns in rust-resistance variation as a result of climate change were not uniform and varied across the geographic scope of the study.